2017
DOI: 10.12688/f1000research.11107.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical activity on the link between PGC-1a and FNDC5 in muscle, circulating Ιrisin and UCP1 of white adipocytes in humans: A systematic review

Abstract: Exercise may activate a brown adipose-like phenotype in white Background: adipose tissue. The aim of this systematic review was to identify the effects of physical activity on the link between peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1a) and fibronectin type III domain-containing protein 5 (FNDC5) in muscle, circulating Irisin and uncoupling protein one (UCP1) of white adipocytes in humans. Two Methods: databases (PubMed 1966 to 08/2016 and EMBASE 1974 to 08/2016 were searched … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 93 publications
4
36
0
Order By: Relevance
“…The signalling pathways that control FNDC5 expression have not been fully elucidated with contradictory results from different in vitro studies [10,11]. For instance, it was reported that exercise-mimicking treatment failed to increase Fndc5 expression in myotubes [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The signalling pathways that control FNDC5 expression have not been fully elucidated with contradictory results from different in vitro studies [10,11]. For instance, it was reported that exercise-mimicking treatment failed to increase Fndc5 expression in myotubes [34].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, contradictory results were obtained from different laboratories that activation of PGC-1α and FNDC5 expressions were uncoupled in skeletal muscle during exercise [10]. In 2017, a meta-analysis including 51 studies reported that a solid conclusion could not be made about the link between PGC-1α activity and FNDC5 expression in response to physical activity [11]. Thus, the molecular mechanisms of exercise-regulated FNDC5 expression in skeletal muscle are still far from clear.…”
Section: Introductionmentioning
confidence: 99%
“…AMPK activation during exercise is one of the factors involved in increasing PGC-1α and irisin levels (Chavanelle et al, 2017). AMPK activation leads to the phosphorylation of PGC-1α as a modifier of FNDC5 and irisin secretion (Dinas et al, 2017). Also, PGC-1α activates PPARγ, which is involved in energy metabolism and stimulates increases in FNDC5 and irisin (Panati et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Exercise has numerous influences on multiple gut peptides and consequently energy balance (Dorling et al, 2018). Studies have investigated the effects of different modes of exercise training on PGC-1α (Dinas et al, 2017;Jung and Kim, 2014;Norheim et al, 2014), irisin (Dinas et al, 2017;Norheim et al, 2014;Samy et al, 2015), nesfatin-1 (Algul et al, 2017;Ghanbari Niaki et al, 2013b;Ghanbari-Niaki et al, 2010;Mogharnasi et al, 2018) and resistin (Cobbold, 2018;Shafiee and Sharifi, 2017;García-Hermoso et al, 2017). However, the effects of HMB on these factors have not been investigated widely.…”
Section: Introductionmentioning
confidence: 99%
“…During cold exposure, irisin secretion is increased in a way proportional to shivering intensity, in magnitude similar to exercise‐stimulated secretion (Lee et al, ). Despite the mounting evidence, not all studies agree on the importance of irisin to exercise‐stimulated browning (Dinas et al, ), suggesting that more research needs to be performed in this field before any definite conclusion is made.…”
Section: Proteins/peptidesmentioning
confidence: 99%